A comparative analysis of conventional smear and sure path liquid-based cytology with cell block preparation - Kumar, Sanjay; Saini, Tapasya; Devi, Pinki; Kataria, Sant Prakash; Nanda, Smiti; Singh, Sunita (International Journal of Research in Medical Sciences, 2021)
Background: Cervical cancer is ranked as the most frequent cancer in women in India. Conventional papanicolaou smear has been the mainstay of cervical cancer screening since the 1960s. As an alternative liquid-based cytology (LBC) was introduced in the mid-1990s, which are found to increase cytologic detection of squamous intraepithelial lesions and a reduction in the number of unsatisfactory pap tests. Present study aims at comparison of liquid-based cytology with conventional cytology in detecting uterine cervical intraepithelial lesions. Methods: The present study was conducted in the department of pathology in collaboration with the department of obstetrics and gynecology, Pt. B.D. Sharma PGIMS Rohtak including 100 non-pregnant female patients coming in the outpatient department of obstetrics and gynecology. Both liquid based and conventional pap smears were examined under the microscope and reported according to the 2001 Bethesda system. Cell blocks were prepared sin all the cases from the residual material of LBC. Results: Median age was 42 years. More inadequate smears were reported on CS (17%) as compared to LBC (11%). In both, maximum number of cases reported were inflammatory. Equal number of cases were reported as SCC (n=4) in both. Conclusions: Liquid based cytology has been developed to address the sampling problems of conventional Pap smear. But because of the increased cost of LBC in terms of capital investment, operation and disposables, developing countries should carefully consider the potential benefits and drawbacks of LBC before adopting this new technology.